XPS Depth Study on the Liquid Oxidation of Sn-Bi-Zn-X(Al/P) Alloy and the Effect of Al/P on the Film - X. J. Wang; N. Liu; S. Shi; Y. X. Chen (Advances in Materials Science and Engineering)
X-ray photoelectron spectroscopy (XPS) was used to study the properties of liquid oxidation of Sn-Bi-Zn (SBZ) solder alloys and the effect of Al/P on the oxide film. The results showed that the oxidation film on SBZ surface was in high concentration of both oxygen and zinc. Adding trace amount of Al/P to SBZ alloys (SBZA/ABZP) decreased the ratio of O/M (M could be Sn, Bi, and Al/P) and changed the film compositions. Layers near the free surface of oxidation film mostly contained Zn2+ and Al3+ oxides for SBZA. From the half quantitative analysis result, the aluminum had a surface enrichment behavior in liquid solder, so did phosphorus and zinc. Therefore, the Al/P addition changed their stoichiometry such as the ratio of O/M near film surface.